2018
DOI: 10.1038/s41467-018-07735-4
|View full text |Cite
|
Sign up to set email alerts
|

JunB regulates homeostasis and suppressive functions of effector regulatory T cells

Abstract: Foxp3-expressing CD4+ regulatory T (Treg) cells need to differentiate into effector Treg (eTreg) cells to maintain immune homeostasis. T-cell receptor (TCR)-dependent induction of the transcription factor IRF4 is essential for eTreg differentiation, but how IRF4 activity is regulated in Treg cells is still unclear. Here we show that the AP-1 transcription factor, JunB, is expressed in eTreg cells and promotes an IRF4-dependent transcription program. Mice lacking JunB in Treg cells develop multi-organ autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 57 publications
9
82
2
Order By: Relevance
“…Consistent with the previous study, we found that JunB deficiency decreased the expression of genes encoding the Treg cell effector molecules, such as Icos, Klrg1, Ctla4, and Tigit. These results echo the conclusion in the previous study that JunB pIays an essential role in instructing the Treg effector program [15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with the previous study, we found that JunB deficiency decreased the expression of genes encoding the Treg cell effector molecules, such as Icos, Klrg1, Ctla4, and Tigit. These results echo the conclusion in the previous study that JunB pIays an essential role in instructing the Treg effector program [15].…”
Section: Discussionsupporting
confidence: 92%
“…JunB deficiency caused massive immune cell infiltration into ears and salivary glands. However, we did not observe immune infiltrates in other tissues or organs as reported previously [15]. One possible explanation for this difference is that is that the Junb Flox/Flox mice used in the two studies are not the same.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…the “scurfy” phenotype 21 ). We also observed no spontaneous mortality (up to at least 14 weeks of age; data not shown), which contrasts markedly with the ∼35% lethality in Junb F/F Foxp3 YFP-cre mice reported by Koizumi et al 17 , suggesting that environmental differences may exert a substantial influence on JunB-dependent Treg activity. Taken together, these data suggest that JunB plays a nuanced role in Treg-mediated immune homeostasis.…”
Section: Resultscontrasting
confidence: 70%
“…Previously, we and others found that the AP-1 TF JunB was essential for the differentiation of inflammatory T-helper 17 (Th17) cells 14, 15, 16 , demonstrating that JunB plays subset-restricted roles in T cell programming. More recently, JunB was reported to control differentiation and suppressive functions of eTregs 17 ; however, many of the conclusions from this study are confounded by the use of a CD4-cre-mediated Junb conditional deletion strategy that has since been demonstrated to cause cell-extrinsic defects in Treg development 18 . Because of the predicted role of JunB in tissue-specific Tregs and previous data demonstrating broad and important roles for JunB in Th17 cells, we therefore chose to directly investigate whether JunB was important for tissue-specific functionality in Tregs.…”
Section: Introductionmentioning
confidence: 81%